Ethnomedicinal, phytochemical and pharmacological investigations of Baccharis dracunculifolia DC. (ASTERACEAE) - Gazim, Zilda Cristiani; Valle, Juliana Silveira; Carvalho dos Santos, Isabela; Rahal, Isabelle Luiz; Silva, Gabriela Catuzo Canonico; Lopes, Ana Daniela; Ruiz, Suelen Pereira; Faria, Maria Graciela Iecher; Piau Junior, Ranulfo; Gonçalves, Daniela Dib (Frontiers in Pharmacology, 2022)
Baccharis dracunculifolia DC (Lamiaceae) (Asteraceae) is found in South America, mainly in Argentina, Brazil, Bolivia, Paraguay and Uruguay. Folk medicine is used as a sedative, hypotensive, bronchodilator, cardiovascular disorders, anti-flu, and also in skin wounds. Considered the main source of green propolis, which increases the pharmacological interest in this species. It is also known as a “benefactor” plant facilitating the development of other plant species around it, being indicated for the recovery of degraded areas. This species has been studied for decades in order to isolate and identify the active principles present in the aerial parts (leaves and flowers) and roots. The present study consists of a review of the scientific literature addressing the ethnobotanical, ethnomedicinal, phytochemical, pharmacological and potential cytotoxic effects of the B. dracunculifolia species. In this survey, we sought to investigate issues related to the botanical and geographic description of the species, the ethnobotanical uses, as well as the phytochemical studies of the essential oil, extracts and green propolis obtained from the aerial parts and roots of B. dracunculifolia. Using high precision analytical tools, numerous compounds have already been isolated and identified from leaves and flowers such as the flavonoids: naringenin, acacetin, dihydrokaempferol, isosakuranetin and kaempferide; phenolic acids: p-coumaric, dihydrocoumaric, ferulic, (E)-cinnamic, hydroxycinnamic, gallic, caffeic, and several caffeoylquinic acids derivatives; phenolic acids prenylated: artepillin C, baccharin, drupanin; the glycosides dracuculifosides and the pentacyclic triterpenoids: Baccharis oxide and friedelanol. The predominant class in the essential oil of leaves and flowers are terpenoids comprising oxygenated monoterpenes and sesquiterpenes, highlighting the compounds nerolidol, spathulenol, germacrene D and bicyclogermacrene. These compounds give the species high antimicrobial, antioxidant, antitumor, analgesic, immunomodulatory and antiparasitic potential, making this species a promising herbal medicine. In vitro toxicity assays with B. dracunculifolia extract showed low or no cytotoxicity. However, in vivo analyses with high doses of the aqueous extract resulted in genotoxic effects, which leads us to conclude that the toxicity of this plant is dose-dependent.